Validation of the prognostic value of histologic scoring systems in primary sclerosing cholangitis: An international cohort study - de Vries, Elisabeth M. G.; de Krijger, Manon; Färkkilä, Martti; Arola, Johanna; Schirmacher, Peter; Gotthardt, Daniel; Goeppert, Benjamin; Trivedi, Palak J.; Hirschfield, Gideon M.; Ytting, Henriette; Vainer, Ben; Buuren, Henk R. van; et al. (Hepatology (Baltimore, Md.), 2017)
Histologic scoring systems specific for primary sclerosing cholangitis (PSC) are not validated. We recently determined the applicability and prognostic value of three histological scoring systems in a single PSC cohort. The aim of this study was to validate their prognostic use and reproducibility across a multicenter PSC cohort. Liver biopsies from PSC patients were collected from seven European institutions. Histologic scoring was performed using the Nakanuma, Ishak, and Ludwig scoring systems. Biopsies were independently scored by six liver pathologists for interobserver agreement. The prognostic value of clinical, biochemical, and all three histologic scoring systems on predicting composite endpoints 1 (PSC‐related death and liver transplantation), 2 (liver transplantation), and 3 (liver‐related events), was assessed using univariable and multivariable Cox proportional hazards modeling. A total of 119 PSC patients were identified, and the median follow‐up was 142 months. During follow‐up, 31 patients died (20 PSC‐related deaths), 31 patients underwent liver transplantation, and 35 patients experienced one or more liver‐related events. All three staging systems were independent predictors of endpoints 2 and 3 (Nakanuma system: hazard ratio [HR], 3.16 [95% confidence interval (CI), 1.49‐6.68] for endpoint 2 and HR, 2.05 [95% CI, 1.17‐3.57] for endpoint 3; Ishak system: HR, 1.55 [95% CI, 1.10‐2.18] for endpoint 2 and HR, 1.43 [95% CI, 1.10‐1.85] for endpoint 3; Ludwig system: HR, 2.62 [95% CI, 1.19‐5.80] for endpoint 2 and HR, 2.06 [95% CI, 1.09‐3.89] for endpoint 3). Only the Nakanuma staging system was independently associated with endpoint 1: HR, 2.14 (95% CI, 1.22‐3.77). Interobserver agreement was moderate for Nakanuma stage (κ = 0.56) and substantial for Nakanuma component fibrosis (κ = 0.67), Ishak stage (κ = 0.64), and Ludwig stage (κ = 0.62). Conclusion: We confirm the independent prognostic value and demonstrate for the first time the reproducibility of staging disease progression in PSC using the Nakanuma, Ishak, and Ludwig staging systems. The Nakanuma staging system—incorporating features of chronic biliary disease—again showed the strongest predictive value. (Hepatology 2017;65:907‐919).